Logistics projects based on radio frequency identification: Multi-criteria assessment of Brazilian aircraft industry - de Castro, Jefferson Inácio [UNESP]; Muniz, Jorge [UNESP]; Bernardes, Ednilson; Tramarico, Claudemir Leif [UNESP] (FapUNIFESP (SciELO), 2021)
The purpose of this paper is to investigate the prioritization of Radio Frequency Identification Technology (RFID) logistics projects in a developing economy. This paper adopts a Multi-Criteria Decision-Making (MCDM) method to assess RFID logistics projects. The study examines the use of RFID in the Brazilian aerospace industry and contributes to both the RFID and MDCA literature. The main contribution of this article is to present RFID applications in industrial processes and their strategic approaches, seeking to improve the efficiency, flexibility and the inventory visibility. The approach proposed a decision process to assess RFID logistics projects in the Brazilian aeronautics industry.
Keywords: Aerospace industry; Analytic hierarchy process; Logistics management; Radio frequency technology